Pemberdayaan Ekonomi Lansia melalui Program Sekolah Lansia di Kelurahan Pasir Gunung Selatan, Depok, Jawa Barat - Agustin, Dinni; Nazriah, Ainun (P3M FIA UNKRIS, 2025)
The increasing proportion of older persons in Indonesia requires empowerment programmes that address not only health aspects but also economic independence. Older adults who remain productive tend to experience better physical, psychological, and social well-being. This Community Service Programme (Pengabdian kepada Masyarakat/PKM) aimed to enhance the economic capacity of older adults through an age-friendly economic empowerment intervention. The activity was conducted on 19 November 2025 in Pasir Gunung Selatan Sub-district (PGS), Depok City, West Java, involving 25 older adults participating in the PGS Elderly School. The programme employed educational sessions, participatory discussions, identification of elderly economic potentials, and simple business planning simulations. The results (pre-post test) showed an improvement in participants’ understanding of age-appropriate economic activities, basic financial management, and the importance of productive engagement in later life. In addition, the programme fostered collective awareness among older adults regarding group-based economic activities supported by families and the community. This PKM activity demonstrates the potential of community-based elderly economic empowerment as a sustainable model to support active and healthy ageing.